2022
DOI: 10.1016/j.ophtha.2021.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of 8 Atropine Concentrations for Myopia Control in Children

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
95
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(109 citation statements)
references
References 58 publications
12
95
1
1
Order By: Relevance
“…Moreover, different doses of atropine had a significantly lower OR in children with rapid myopia progression (OR = 0.16, 95% CI = 0.11–0.23, eFigure 4A in the Supplementary Material ) and a significantly higher OR in children with slow myopia progression (OR = 5.88, 95% CI = 3.86–8.95, eFigure 4B in the Supplementary Material ), which was consistent with Ha et al ( 18 ) and our previous meta-analysis published in 2014 ( 15 ).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Moreover, different doses of atropine had a significantly lower OR in children with rapid myopia progression (OR = 0.16, 95% CI = 0.11–0.23, eFigure 4A in the Supplementary Material ) and a significantly higher OR in children with slow myopia progression (OR = 5.88, 95% CI = 3.86–8.95, eFigure 4B in the Supplementary Material ), which was consistent with Ha et al ( 18 ) and our previous meta-analysis published in 2014 ( 15 ).…”
Section: Discussionsupporting
confidence: 90%
“…Previously, few data were available for the quantitative assessment of adverse effects of topical atropine, except the meta-analysis conducted by Gong et al ( 13 ) and Ha et al ( 18 ), which showed that a higher dose of atropine led to an increasing number of adverse effects. Our results also demonstrated that the side effects of atropine, such as photophobia was dose-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations